2020
DOI: 10.3390/biom10111495
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Levels of a Cleaved Form of Galectin-9 Are the Most Sensitive Biomarkers of Acquired Immune Deficiency Syndrome and Tuberculosis Coinfection

Abstract: Acquired immunodeficiency syndrome (AIDS) complicated with tuberculosis (TB) is a global public issue. Due to the paucity of bacteria in AIDS/TB, blood-based biomarkers that reflect disease severity are desired. Plasma levels of matricellular proteins, such as osteopontin (OPN) and galectin-9 (Gal-9), are known to be elevated in AIDS and TB. Therefore, full-length (FL)-Gal9 and FL-OPN, and their truncated forms (Tr-Gal9, Ud-OPN), and 38 cytokines/chemokines were measured in the plasma of 24 AIDS (other than TB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 32 publications
1
20
0
Order By: Relevance
“…This might be related to their hyperimmune activation status or infection-associated indirect cell damage. Gal-9 is reported to be degraded swiftly by proteinases (47). This might be a protective mechanism to prevent off-target effects of this immunomodulatory protein.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This might be related to their hyperimmune activation status or infection-associated indirect cell damage. Gal-9 is reported to be degraded swiftly by proteinases (47). This might be a protective mechanism to prevent off-target effects of this immunomodulatory protein.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, it has been reported that the fulllength Gal-9 (F-Gal-9) levels were extremely elevated in dengue fever (38). However, the cleaved/truncated from of Gal-9 (T-Gal-9) was considered a more sensitive biomarker to distinguish HIV-infected individuals from those coinfected with tuberculosis (47). Therefore, it would be worth examining F-Gal-9 versus T-Gal-9 levels in COVID-19 patients since the R&D Systems ELISA kit quantifies both forms of Gal-9.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, an assay to measure the cleaved form of Gal-9 was developed [ 50 ]. A biomarker analysis conducted in patients with HIV/OI revealed that levels of Tr-Gal-9 markedly reflect the disease severity of the co-infected individuals [ 53 , 96 ]. The Tr-Gal-9 may be generated via cleavage by MMP-9, which has also been proposed to be a non-sputum-based biomarker for differentiating pulmonary TB and extrapulmonary TB [ 97 ].…”
Section: Galectin-9 In a Variety Of Infectious Diseasesmentioning
confidence: 99%
“…Furthermore, it was demonstrated that the exposure to lipoarabinomannan (LAM), a lipid virulence factor secreted by M. tuberculosis , of monocytes during differentiation toward macrophages downregulates their Gal-9 expression, consequently leading to the development of monocyte-derived macrophages (MDM) with a reduced capacity to respond to inflammatory stimuli and restrict M. tuberculosis growth [ 132 ]. Recent study indicated that the plasma levels of Gal-9 in TB patients was significantly higher compared with healthy control subjects ( Table 1 ) and proposed Gal-9 as a biomarker for TB [ 53 ].…”
Section: Galectin-9 In a Variety Of Infectious Diseasesmentioning
confidence: 99%
“…We previously reported that analysis by enzyme-linked immunosorbent assay (ELISA) differentiated between the levels of the cleaved form of OPN (undefined (Ud)-OPN) and FL-OPN [ 27 ]. Recently, we established the ELISA system which can differentiate the truncated form of Gal-9 (Tr-Gal9) and FL-Gal9 [ 34 ], and reported that plasma levels of Tr-Gal9 reflected inflammation and the severity of disease in acquired immunodeficiency syndrome (AIDS) and AIDS associated with tuberculosis (AIDS/TB) patients [ 35 ].…”
Section: Introductionmentioning
confidence: 99%